Efficacy, Safety and Tolerability Evaluation of Global Healing Center-s Oxy Powder® in Treating Irritable Bowel Syndrome (Constipation - Predominant) (IBS-C) - JOGENDER K. LALLA; DEVEN V.PARMAR; MEENA U.SHAH; EDWARD III GROUP (International Journal of Pharma and Bio Sciences, 2010)
An open, randomized, comparative, Phase II clinical trial on 20 patients with Constipation – Predominant Irritable Bowel Syndrome (IBS–C) was conducted for 6 weeks for evaluating safety, tolerability and efficacy of Oxy Powder® (OP) compared with Dulcolax (DX) tablets. The results indicated that complete cure was obtained in 30.8% and improvement in 69.2% patients treated with OP. In case of DX, improvement was seen in 71.4% patients and failure in 28.6% patients. There was no failure in case of OP indicating that efficacy of OP in treating IBS–C was significantly higher (p<.05) than DX.